Cricopharyngeal achalasia: Surgical treatment. Three cases - Garcia Pierce, Héctor; Carriquiry, Luis A.; Olivera, Daniel; Bergalli, Luis; Blasiak, José; Pradines, Jorge (Cirugía del Uruguay, 1978)
The authors present a series of three cases of cricopharyngeal achalasia. This is a functional disorder brought about by a continous contraction of muscle cricopharingeus. The paper includes the most common elements in its physiopathology arid most usual therapy: extramucous miosection of cricopharyngeus.